Ser protagonista: produção colaborativa de textos em língua inglesa - Cagliari, Diane Carla (2016)
Language teaching has several possibilities for support since there has been a wide variety of technologies present in the virtual learning environments. This study aims to provide participating students of Clube de Relações Internacionais Garança, in the Military School, a way to produce, collaboratively, texts in English that allow greater interaction, learning and autonomy during the development of the group activities. By using Educational Technology Network, it is possible to reach the needs of collaborative writing of students within the context in which they live. It is an action research, as this methodology produces an understanding of the school environment as it is considered emancipatory. Besides, it may produce changes in the pedagogical practices in the classroom. The product of this study is an infographic of How to Use GoogleDocs to improve collaborative writing. It was possible to identify that students are open to new experience of using technology in order to improve the writing process. Using an online tool as a mechanism to challenge students to write collaboratively enabled the rising of knowledge. Collaborative writing is not widely used in English classes, but the tool has proved to be a possibility of instigating the students to participate in the writing of his colleagues.